Silicon carbide boat support and preparation method and application thereof
By adding SiO2 and B2O3 to the silicon carbide boat holder, and using multiple ball milling treatments and powder compounding of different particle sizes, the thermal stress problem of the boat holder under extremely high temperatures and rapid temperature changes is solved, and its corrosion resistance and service life are improved.
Patent Information
- Application Number
- CN202411875461.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-08
AI Technical Summary
Existing silicon carbide boat holders may generate thermal stress at extremely high temperatures and rapid temperature changes, resulting in structural changes or damage. At the same time, they are prone to corrosion in the environment of chemicals and high-temperature gases, affecting their service life.
By adding SiO2 and B2O3, combined with multiple ball milling treatments and compounding of powders of different particle sizes, the lattice defects and number of Si vacancy of the material are regulated, and the lattice structure is optimized to improve fluidity and reactivity, reduce sintering temperature and reduce thermal stress. Y2O3 acts as a stabilizer to improve chemical stability and structural integrity.
It realizes effective sintering at lower temperatures, reduces the thermal stress of the boat support at high temperatures, maintains the integrity of the structure, and improves its corrosion resistance and service life.
Smart Images

Figure BDA0005198031780000131 
Figure BDA0005198031780000141 
Figure BDA0005198031780000151
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of boat support production, and in particular to a silicon carbide boat support and a preparation method and application thereof. Background Art
[0002] With the rapid growth of global demand for renewable energy, the photovoltaic industry, as an important component of clean energy, is experiencing unprecedented development. As the core component of the photovoltaic system, the production efficiency and product quality of photovoltaic cells directly determine the power generation efficiency and economic benefits of the entire photovoltaic system. In the manufacturing process of photovoltaic cells, high-temperature treatment is a crucial link, which involves placing silicon wafers in high-temperature furnace tubes for heat treatment to form the required electrical properties and structures. In this process, the boat support is a carrier that carries silicon wafers through high-temperature furnace tubes. Its performance and quality have a crucial impact on the production efficiency and yield rate of the cell. Traditional boat supports are mostly made of quartz materials, but quartz materials are prone to deformation at high temperatures, causing the position of silicon wafers to shift, which in turn affects the performance and quality of the cell. In addition, the thermal conductivity of quartz materials is relatively low, and the heat dissipation effect is poor, which can easily lead to excessive internal temperature of the boat support, further exacerbating the deformation problem.
[0003] In order to overcome the shortcomings of quartz boat supports, manufacturers have gradually begun to use silicon carbide materials to make boat supports. Silicon carbide materials have excellent high temperature resistance, good thermal conductivity and chemical stability, can maintain structural stability at high temperatures, and are not easy to deform. However, the existing silicon carbide boat supports still have some shortcomings in manufacturing. For example, silicon carbide boat supports may still produce thermal stress under extremely high temperatures and rapid temperature changes, resulting in changes or damage to the boat support structure; in addition, the boat support may be exposed to various chemicals and high-temperature gases. These environmental factors may corrode the silicon carbide material and affect its service life. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing a silicon carbide boat support and a preparation method and application thereof, so as to improve the high temperature resistance and corrosion resistance of the boat support.
[0005] In a first aspect, an embodiment of the present application provides a silicon carbide boat support, comprising a β-SiC raw material, a stabilizer, a flux and a sintering aid; wherein the sintering aid comprises SiO2, the flux comprises B2O3, and the stabilizer comprises Y2O3.
[0006] This application adds SiO2 and B2O3, and under the synergistic effect of the two, the lattice defects and the number of Si vacancies of the material can be regulated; the optimized lattice structure can improve the fluidity and reactivity of the material, so that it can achieve effective particle bonding at a lower temperature, so that the desired sintering effect can be achieved at a lower temperature, thereby reducing the sintering temperature, and reducing the thermal stress of the boat support at high temperature to maintain the integrity of the boat support. Among them, the addition of B2O3 can regulate the number of Si vacancies in the lattice, and a small amount of Si vacancies can significantly improve the thermal conductivity of the material; SiO2 is the source of lattice oxygen in SiC, and the interaction between the lattice oxygen and Si vacancies generated by the reaction with SiC during the sintering process promotes the efficiency of heat conduction; at the same time, suppressing lattice oxygen is equivalent to suppressing Si vacancies, thereby reducing phonon scattering and further improving thermal conductivity. Moreover, SiO2 and B2O3 will melt and fill the gaps between particles during the sintering process, promoting the contact and bonding of particles. By reducing the adhesion energy between particles, the temperature required for solid phase sintering is reduced, and the densification of the material is promoted and the density of the material is increased, thereby enhancing its high temperature resistance. The regulation of Si vacancies and oxygen in the lattice improves the thermal expansion performance of the boat support when the temperature changes, reduces the structural damage caused by thermal stress, and maintains the integrity of the boat support. In addition, the addition of Y2O3 as a stabilizer not only improves the chemical stability of the boat support, but also enhances the structural integrity under high temperature conditions.
[0007] In some embodiments of the present application, the composition comprises, by mass percentage, 98-98.8% β-SiC, 0.3-0.5% Y2O3, 0.3-0.5% B2O3 and 0.6-1% SiO2.
[0008] In some embodiments of the present application, the composition includes, by mass percentage, 98% β-SiC, 0.5% Y2O3, 0.5% B2O3 and 1% SiO2.
[0009] In the second aspect, an embodiment of the present application provides a method for preparing the above-mentioned silicon carbide boat support, comprising: mixing the raw materials according to a ratio, performing a first ball milling treatment to obtain a slurry; drying the slurry and performing a first sieving treatment to obtain a dry powder, and dividing the dry powder into two parts, dry powder A and dry powder B; performing a second ball milling treatment on the dry powder A, adding dry powder B after the second ball milling treatment, performing a third ball milling treatment to obtain a ball-milled powder, drying the ball-milled powder and performing a second sieving treatment to obtain a mixed powder; molding the mixed powder to obtain a ceramic blank; sintering and annealing the ceramic blank to obtain a silicon carbide boat support; wherein the particle size of the dry powder is greater than the particle size of the mixed powder.
[0010] In the preparation method of the present application, a dry powder with a larger particle size is obtained after the first ball milling treatment and screening; the dry powder is then divided into two parts, dry powder A and dry powder B, and the dry powder A is subjected to a second ball milling treatment to further reduce its particle size; finally, the dry powder A with a larger particle size and the dry powder B after the second ball milling are mixed through a third ball milling, so that the obtained ball milled powder contains particles of different particle sizes at the same time; among them, the larger dry powder A particles provide good mechanical support, and the presence of large particles reduces the deformation and defects that may be caused by particle shrinkage during high-temperature sintering, thereby improving the density and integrity of the final product; in addition, the larger particles can effectively reduce the surface energy and reduce the agglomeration of the material during the sintering process, thereby improving the uniformity of sintering; compared with large particles, small particles have higher surface energy and stronger sintering activity, and small particles can react and combine faster during the sintering process. This high reactivity helps to achieve effective sintering at a lower temperature. Therefore, the present application compounds powders of different particle sizes so that the material can maintain good mechanical support during the sintering process and fully utilize the high sintering activity of small particles, thereby reducing the sintering temperature while ensuring structural stability; the support effect of large particles is combined with the reactivity of small particles, which effectively avoids agglomeration, promotes close contact between particles, and improves the density and uniformity of the material.
[0011] In some embodiments of the present application, in the first screening, the mesh number of the sieve is 60-80 mesh; and / or, in the second screening, the mesh number of the sieve is 180-200 mesh.
[0012] The first screening (60-80 mesh) can remove larger particles and impurities, making the particle size distribution of the material for subsequent processing more uniform. This helps to improve the overall quality and performance of the material. Smaller particles help to increase the specific surface area and promote close contact between particles, thereby achieving better bonding during the sintering process. In addition, removing large particles can avoid defects that may occur during the sintering process, such as cracks or voids. The second screening (180-200 mesh) further refines the mixed powder to make the particle size more uniform, especially for the optimization of small particles. Fine particles have higher surface energy and sintering activity, and can achieve effective sintering at lower temperatures. This refinement process helps to reduce the sintering temperature, improve sintering efficiency, and reduce energy consumption.
[0013] In some embodiments of the present application, in the above-mentioned dry powder, the mass proportion of dry powder A is 18-25%; and / or the mass proportion of dry powder B is 75-82%.
[0014] The smaller proportion of dry powder A (18-25%) is mainly used to provide mechanical support and improve the stability of the overall structure. The appropriate addition of dry powder A can prevent deformation caused by excessive shrinkage during the sintering process, thereby maintaining the shape and integrity of the final product; the larger dry powder B (75-82%) improves the density and uniformity of the overall material. The higher proportion of dry powder B helps to improve the reactivity of the material and promote sintering at a lower temperature. At the same time, the addition of dry powder A can effectively improve the fluidity and the bonding force between particles during the sintering process, and further reduce the sintering temperature. Therefore, by controlling the ratio of dry powder A and dry powder B within the above range, the sintering activity and sintering temperature of the material can be adjusted. At the same time, a higher proportion of dry powder B (75-82%) helps to maintain the fluidity of the material, reduce adhesion between particles, and better combine the particles during the sintering process, thereby improving the uniformity and density of the final product.
[0015] In some embodiments of the present application, the conditions for the first ball milling treatment include: the ball milling speed is 3-5rad / s, and the ball milling time is 10-16h; and / or, the conditions for the second ball milling treatment include: the ball milling speed is 6-10rad / s, and the ball milling time is 2-5h; and / or, the conditions for the third ball milling treatment include: the ball milling speed is 3-5rad / s, and the ball milling time is 10-16h.
[0016] The lower speed and longer time of the first ball milling treatment are designed to achieve preliminary material mixing and particle refinement. The higher speed and shorter time of the second ball milling treatment are designed to further refine the particles and enhance the sintering activity. The third ball milling treatment aims to evenly mix the powders of different particle sizes produced by the first two ball milling treatments.
[0017] In some embodiments of the present application, sintering includes: placing the ceramic green body in a container, heating the temperature to 1500-1600° C. at a heating rate of 4-6° C. / min, and then keeping the temperature for 31-41 hours.
[0018] The slow heating rate (4-6℃ / min) is intended to prevent thermal stress and cracks caused by rapid temperature changes. The temperature is raised to 1500-1600℃ to allow the ceramic green body to be fully sintered. The temperature is kept for 31-41 hours to allow the material to fully react and sinter.
[0019] In some embodiments of the present application, the annealing temperature is 1150-1250° C., and the annealing time is 3-6 hours.
[0020] Controlling the annealing temperature and time within the above range can effectively reduce the stress inside the material and reduce the risk of cracking and deformation, thereby improving the overall stability and reliability of the product. It can also make the microstructure inside the material more uniform and improve the overall performance of the material.
[0021] In a third aspect, an embodiment of the present application provides an application of any of the above-mentioned silicon carbide boat supports in the production of photovoltaic cells. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0023] The following is a detailed description of a silicon carbide boat support and its preparation method and application according to an embodiment of the present application.
[0024] The present application provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0025] (1) After the raw materials are mixed evenly according to the corresponding proportions, they are placed in a ball mill and subjected to the first ball milling treatment to obtain a slurry. The anhydrous ethanol, the mixed raw materials and the ball milling beads are mixed in a certain proportion, for example: anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1, which can be adjusted as needed and is not limited in this application.
[0026] The raw materials of the silicon carbide boat support include β-SiC raw material, stabilizer, flux and sintering aid; wherein the sintering aid includes SiO2, the flux includes B2O3, and the stabilizer includes Y2O3.
[0027] Studies have shown that for polycrystalline materials, factors such as lattice defects, grain size, additives, and phase changes all affect the thermal conductivity of the material, and high thermal conductivity is the result of multi-factor coupling. This application uses B2O3 to regulate the number of lattice Si vacancies. The presence of a small amount of Si vacancies in the lattice has a significant effect on improving thermal conductivity. SiO2 is the source of lattice oxygen in SiC. When SiO2 surrounded by SiC is sintered, lattice oxygen at the C atomic site and related Si vacancies are formed in expression (1). Due to the considerable mass contrast and lattice mismatch between Si and vacancies, strong phonon scattering occurs at Si vacancies. Therefore, suppressing lattice oxygen, which is equivalent to suppressing Si vacancies, is an effective strategy to improve thermal conductivity.
[0028] SiO2→Si Si × +2O C ·· +V Si ″″------------------------(1)
[0029] In the embodiment of the present application, the composition includes, by mass percentage, 98-98.8% β-SiC, 0.3-0.5% Y2O3, 0.3-0.5% B2O3 and 0.6-1% SiO2.
[0030] As an example, in terms of mass percentage, it includes: 98% β-SiC, 0.5% Y2O3, 0.5% B2O3 and 1% SiO2.
[0031] In the first ball milling treatment, the ball milling speed is 3-5 rad / s, and the ball milling time is 10-16 h.
[0032] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, the mesh number of the screen is 60-80 mesh, to obtain dry powder, and the dry powder is divided into two parts: dry powder A and dry powder B; dry powder A is subjected to a second ball milling treatment, and after the second ball milling treatment is completed, dry powder B is added and subjected to a third ball milling treatment to obtain ball milled powder, and the ball milled powder is dried and screened for the second time, the mesh number of the screen is 180-200 mesh, to obtain a mixed powder; wherein the particle size of the dry powder is greater than the particle size of the mixed powder.
[0033] In the above dry powder, the mass proportion of dry powder A is 18-25%, and the mass proportion of dry powder B is 75-82%. As an example, in the above dry powder, the mass proportion of dry powder A is 20%, and the mass proportion of dry powder B is 80%, which can be adjusted as needed and is not limited in this application.
[0034] The conditions for the second ball milling treatment include: a ball milling speed of 6-8 rad / s, and a ball milling time of 4-8 h; the conditions for the third ball milling treatment include: a ball milling speed of 3-5 rad / s, and a ball milling time of 10-16 h.
[0035] For the first ball milling treatment, the ball milling speed is 3-5rad / s and the ball milling time is 10-16h. The slower speed is conducive to the full mixing of the materials and the uniform distribution of the components. The longer ball milling time can effectively break up the large particles, refine the materials, and increase the specific surface area, laying a good foundation for the subsequent sintering process. For the second ball milling treatment, the ball milling speed is 6-8rad / s and the ball milling time is 4-8h. The higher speed increases the impact force of the grinding balls, which helps to further refine the particles, thereby enhancing the sintering activity of the materials and promoting effective sintering at lower temperatures. The short-term treatment reduces the residence time of the particles in the abrasive, reduces the agglomeration phenomenon, and ensures the uniformity and fluidity of the particles. The third ball milling treatment is to evenly mix the powders of different particle sizes produced by the first two ball millings.
[0036] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1500-1600°C at a heating rate of 4-6°C / min, and then keeping it warm for 31-41 hours; then cooling it to room temperature with the furnace, and annealing it at 1150-1250°C for 3-6 hours to obtain a silicon carbide boat support.
[0037] A slow heating rate (4-6°C / min) can reduce the temperature gradient in the ceramic blank, reduce internal stress, thereby reducing the risk of cracking and ensuring the integrity of the material during the sintering process. Controlling the heating rate within the above range helps to evenly distribute the temperature of the entire blank during the heating process, further improving the sintering quality. Raising the temperature to 1500-1600°C helps to achieve effective bonding between particles and improve the density and strength of the material. Within this temperature range, materials such as silicon carbide can undergo necessary phase changes, promote the optimization of the crystal structure, and improve thermal conductivity and high temperature resistance. Keeping warm for 31-41 hours further enhances the bonding force between particles, improves the density and uniformity of the material, and reduces porosity; it also helps to stabilize the microstructure inside the material and improve the mechanical strength, high temperature resistance and corrosion resistance of the final product. The annealing process of this application aims to eliminate internal stress, promote grain growth, improve chemical stability, optimize sintering effects, and improve production efficiency and product quality by setting a temperature of 1150-1250°C and a time of 3-6 hours.
[0038] At present, when silicon carbide ceramics are prepared by solid-state sintering, a sintering temperature higher than 2050°C is usually required to overcome its low self-diffusion coefficient (C and Si are 8.62×10 5 and 5.01×10 2 cm 2 / s) to form dense ceramics, which is too difficult and costly to produce. Although liquid-phase sintered silicon carbide ceramics can be sintered at temperatures below 2000°C, they have high requirements for the purity of raw materials, low fracture toughness of sintered bodies, and strong crack strength sensitivity. The ceramic liquid-phase sintering process is usually more complicated and requires precise control of parameters such as temperature, atmosphere, and reaction time, which increases the difficulty and cost of preparation. At the same time, the preparation of the precursor is also a time-consuming and inefficient process, which further affects the industrial application of the liquid-phase sintering method. In the preparation method of the present application, by adding B2O3 and SiO2, through the synergistic effect of the two, and through multiple ball milling, the particle size of the raw material powder is controlled, and the particle size distribution is reasonably designed, giving full play to the mechanical support of large particles and the high sintering activity of small particles, effectively reducing the sintering temperature, and finally achieving solid-state sintering at normal pressure at a temperature below 2000°C; avoiding agglomeration, improving the density and uniformity of the material, so that the prepared boat support has good thermal conductivity, high temperature resistance and corrosion resistance.
[0039] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0040] Example 1
[0041] This embodiment provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0042] (1) β-SiC, B2O3 (purity of 98%), SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 98wt% SiC+0.5wt% Y2O3+0.5wt% B2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0043] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 20%) and dry powder B (accounting for 80%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 8 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0044] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0045] Example 2
[0046] This embodiment provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0047] (1) β-SiC, B2O3 (purity of 98%), SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 98wt% SiC+0.5wt% Y2O3+0.5wt% B2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0048] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 30%) and dry powder B (accounting for 70%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 8 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0049] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0050] Example 3
[0051] This embodiment provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0052] (1) β-SiC, B2O3 (purity of 98%), SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 98wt% SiC+0.5wt% Y2O3+0.5wt% B2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0053] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 12%) and dry powder B (accounting for 88%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 8 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0054] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0055] Example 4
[0056] This embodiment provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0057] (1) β-SiC, B2O3 (purity of 98%), SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 98wt% SiC+0.5wt% Y2O3+0.5wt% B2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0058] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 20%) and dry powder B (accounting for 80%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 6 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0059] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0060] Example 5
[0061] This embodiment provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0062] (1) β-SiC, B2O3 (purity of 98%), SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 98wt% SiC+0.5wt% Y2O3+0.5wt% B2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0063] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 20%) and dry powder B (accounting for 80%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 10 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0064] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0065] Comparative Example 1
[0066] This comparative example provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0067] (1) β-SiC, B2O3 (purity of 98%), SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 98wt% SiC+0.5wt% Y2O3+0.5wt% B2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0068] (2) adding a high temperature resistant epoxy resin to the mixed powder after ball milling in step (1) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0069] Comparative Example 2
[0070] This comparative example is the same as Example 1, except that no B2O3 is added.
[0071] This comparative example provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0072] (1) β-SiC, SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed uniformly according to the chemical composition of 98.5wt% SiC+0.5wt% Y2O3+1wt% SiO2, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0073] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 20%) and dry powder B (accounting for 80%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 8 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0074] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0075] Comparative Example 3
[0076] This comparative example is the same as Example 1, except that no B2O3 is added.
[0077] This comparative example provides a silicon carbide boat support, and the preparation method thereof comprises the following steps:
[0078] (1) β-SiC, SiO2 (purity of 99%), and Y2O3 (purity of 99.9%) are mixed according to the chemical composition of 99wt% SiC+0.5wt% Y2O3+0.5wt% B2O3, and then placed in a ball mill; anhydrous ethanol, mixed raw materials, and ball milling beads are subjected to a first ball milling treatment in a ratio of anhydrous ethanol: mixed raw materials: ball milling beads = 1:1:1 to obtain a slurry; wherein the ball milling speed is 4rad / s, and the ball milling time is 12h.
[0079] (2) The slurry after ball milling in step (1) is placed in a rotary drying device for drying, and then screened for the first time, with a mesh size of 60, to obtain dry powder, and the dry powder is divided into two parts: dry powder A (accounting for 20%) and dry powder B (accounting for 80%); dry powder A is subjected to a second ball milling treatment, wherein the ball milling speed is 8 rad / s and the ball milling time is 4 h; after the second ball milling treatment is completed, dry powder B is added and a third ball milling treatment is performed, wherein the ball milling speed is 4 rad / s and the ball milling time is 12 h; ball milled powder is obtained, and the ball milled powder is dried and screened for the second time, with a mesh size of 200, to obtain a mixed powder.
[0080] (3) Adding high temperature resistant epoxy resin to the mixed powder in step (2) and placing it in a ceramic injection molding machine to obtain a ceramic blank; placing the ceramic blank in a container, heating it to 1550°C at a heating rate of 5°C / min, and then keeping it warm for 36 hours; then cooling it to room temperature with the furnace, and annealing it at 1200°C for 4 hours to obtain a silicon carbide boat support.
[0081] The above-mentioned Examples 1-5 and Comparative Examples 1-3 are basically the same as Example 1, except that the raw material ratios and some preparation parameters are different. Please see Table 1 for details of some parameters.
[0082] Table 1
[0083]
[0084]
[0085] Test example
[0086] In this test example, the above-mentioned embodiments 1-5 and comparative examples 1-3 were subjected to performance tests, including density, porosity, linear expansion coefficient and chemical immersion loss rate.
[0087] Among them, the density is determined by referring to the apparent porosity and capacity test method of porous ceramics in GB / T1966-1996 to measure the volume density and porosity, and then calculating by volume density / theoretical density.
[0088] Determination method of linear expansion coefficient: GB / T 16535-2008 fine ceramic linear thermal expansion coefficient test method is adopted.
[0089] Chemical immersion loss rate determination method: Place the sample in 75% hydrochloric acid at 60°C for 24 hours, and then observe and measure the mass change of the sample. Chemical immersion loss rate = (M0-M f ) / M0×100%, where M0 is the initial mass of the sample before immersion (unit: g); M f : Final mass of the sample after immersion (unit: g).
[0090] Thermal conductivity measurement method: refer to GB / T 32064-2015 for measurement.
[0091] Please see Table 2 for the above performance test results.
[0092] Table 2
[0093]
[0094] It can be seen from Table 2 that the silicon carbide boat support provided in Example 1 of the present application has a higher density (97.5%) and a lower linear expansion coefficient (3.9×10 -6 ℃ -1 ), indicating that the silicon carbide boat support has a tight internal structure, few defects, and good thermal conductivity; and has high mechanical strength, and is less likely to break or deform when subjected to external force; the low linear expansion coefficient shows that it deforms less when the temperature changes, can effectively resist thermal stress, and has good high temperature resistance. At the same time, the silicon carbide boat support provided in Example 1 of the present application has a low porosity (0.2%) and chemical immersion loss rate (1.1%), which shows that the silicon carbide boat support has good corrosion resistance.
[0095] In Comparative Example 1, the second and third ball millings were not performed, resulting in the powder particles being too large and the sintering activity being low, which in turn resulted in the low density, high porosity, chemical immersion loss rate and linear expansion coefficient.
[0096] By comparing Example 1, Comparative Example 2 and Comparative Example 3, it can be found that without adding the sintering aid B2O3, it can be seen that the thermal conductivity is significantly reduced; without adding SiO2, more silicon vacancies result in strong phonon scattering, which in turn leads to a decrease in thermal conductivity.
[0097] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A silicon carbide boat support, characterized in that: Including β-SiC raw materials, stabilizers, flux and sintering aids; Wherein, the sintering aid includes SiO2, the flux includes B2O3, and the stabilizer includes Y2O3.
2. The silicon carbide boat support according to claim 1, characterized in that: Calculated by mass percentage, it comprises: 98-98.8% β-SiC, 0.3-0.5% Y2O3, 0.3-0.5% B2O3 and 0.6-1% SiO2.
3. The silicon carbide boat support according to claim 2, characterized in that: Calculated by mass percentage, it includes: 98% β-SiC, 0.5% Y2O3, 0.5% B2O3 and 1% SiO2.
4. A method for preparing a silicon carbide boat support as claimed in any one of claims 1 to 3, characterized in that: include: The raw materials are mixed according to the proportions, and the first ball milling process is performed to obtain a slurry; After drying the slurry, sieving it for the first time to obtain dry powder, and dividing the dry powder into two parts: dry powder A and dry powder B; The dry powder A is subjected to a second ball milling treatment, after which the dry powder B is added and subjected to a third ball milling treatment to obtain a ball milled powder, and the ball milled powder is dried and sieved for a second time to obtain a mixed powder; The ball-milled powder is subjected to molding treatment to obtain a ceramic blank; the ceramic blank is subjected to sintering and annealing treatment to obtain the silicon carbide boat support; Wherein, the particle size of the dry powder is greater than the particle size of the mixed powder.
5. The preparation method according to claim 4, characterized in that: In the first screening, the mesh size of the sieve is 60-80 mesh; And / or, in the second screening, the mesh size of the sieve is 180-200 meshes.
6. The preparation method according to claim 5, characterized in that: In the dry powder, the mass proportion of the dry powder A is 18-25%; and / or the mass proportion of the dry powder B is 75-82%.
7. The preparation method according to claim 5, characterized in that: The conditions of the first ball milling treatment include: a ball milling speed of 3-5 rad / s and a ball milling time of 10-16 h; And / or, the conditions of the second ball milling treatment include: a ball milling speed of 6-10 rad / s and a ball milling time of 2-5 h; And / or, the conditions of the third ball milling treatment include: a ball milling speed of 3-5 rad / s, and a ball milling time of 10-16 h.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The sintering comprises: The ceramic blank is placed in a container, heated to 1500-1600° C. at a heating rate of 4-6° C. / min, and then kept warm for 31-41 hours.
9. The preparation method according to any one of claims 4 to 7, characterized in that: The annealing temperature is 1150-1250° C., and the annealing time is 3-6 hours.
10. Use of the silicon carbide boat support as claimed in any one of claims 1 to 3 in the production of photovoltaic cells.